Comparing effects of wearable robot-assisted gait training on functional changes and neuroplasticity: A preliminary study. - Jungsoo Lee; Kassymzhomart Kunanbayev; Donggon Jang; Dae-Shik Kim (PLoS ONE)
Robot-assisted gait training (RAGT) is a promising technique for improving the gait ability of elderly adults and patients with gait disorders by enabling high-intensive and task-specific training. Gait functions involve multiple brain regions and networks. Therefore, RAGT is expected to affect not just gait performance but also neuroplasticity and cognitive ability. The purpose of this preliminary study was to verify the feasibility of the proposed RAGT design and to assess and compare the effect sizes of various measurement variables, including physical, cognitive, and neuroimaging induced by RAGT. Twelve healthy adults without any neurological or musculoskeletal disorders participated in this study. All participants wore a wearable exoskeleton robot and underwent 10 RAGT sessions. Functional data related to physical and cognitive abilities and neuroimaging data obtained from a magnetic resonance imaging (MRI) scanner and a functional near-infrared spectroscopy (fNIRS) device were acquired before and after the training sessions to assess the effect sizes of variables affected by RAGT. All participants underwent 10 sessions of RAGT without any adverse incidents, and the feasibility of the proposed RAGT design, consisting of preferred speed walking, fast speed walking, inclined walking, and squats, was validated. Variables related to physical and cognitive abilities significantly improved, but those related to neuroplasticity did not. The effect size of physical ability was "very large," whereas that of cognitive ability was "medium-to-large." The effect sizes of functional and structural neuroplasticity showed "medium" and "very small," respectively. The effect size of the RAGT varied depending on the measured variables, with the effect size being the greatest for physical ability, followed by cognitive ability, functional neuroplasticity, and structural neuroplasticity. The proposed RAGT design affects cognitive and neuroplastic effects beyond the physical effect directly affected by RAGT. This study highlights that while RAGT can positively influence cognitive outcomes beyond physical benefits, more intensive interventions may be required to elicit significant neuroplastic changes. This preliminary study offers useful information for researchers interested in designing robot-assisted training by investigating the potential extent of neuroplastic effects. Trial registration: KCT0006738.